Elemental composition of solid dental deposits in patients with somatic pathology - R. V. Polyakova; N. A. Nikolaev; V. B. Nedoseko (Эндодонтия Today, 2019)
For a number of systemic diseases accompanied by changes in the state of organs and tissues of the oral cavity, manifested more active over carious diseases, lesions of the oral mucosa and periodontal, dental plaque formation. Correlation analysis carried out in the ratio of chemical elements in dental plaque in patients with essential hypertension (EH), diabetes mellitus (DM) and chronic pyelonephritis (KP). In individuals with different somatic diseases established differences in the ratio of chemical elements in the dental plaque. It proved that for hypertensive patients characterized by an increased content of cadmium, vanadium, selenium, and molybdenum, with reduced content of rubidium, silver, barium and chromium, diabetics have a higher content of copper and cadmium, and patients with chronic pyelonephritis distinguishes high content of cesium, indium, vanadium and arsenic under reduced content of silver, titanium, chromium, manganese and bromine. Solid dental deposits are irritating to the gum, the retention points are for the accumulation of dental plaque, disrupt the process of self-purification of the periodontal pocket. The elemental composition of dental plaque was studied on the equipment, the accredited Academy of Sciences to carry out research of the biological profile.